(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
In recent years much more attention has gained by antiviral drugs because of severe acute respiratory syndrome coronavirus-2 (SARS-CoV) infection. Molnupiravir is one of the favorable drugs for SARS-CoV-2 treatment. The present study aimed to develop and validate a simple, rapid, stable, selective, sensitive, accurate, robust, and economical RP-HPLC method for determining molnupiravir in its capsule dosage form. The chromatographic separation was achieved on inert sustain C18 column (250 mm x 4.6 mm x 5 μ) at 40°. Isocratic elution was performed with 25 mM KH2PO4 buffer (pH 3.0) and methanol (60:40 v/v) as mobile phase at flow rate of 1.0 mL/min with 50 μL injection volume. The detection was conceded out at 242 nm. The developed RP-HPLC method yielded a suitable retention time of 4.2 minutes for molnupiravir. The developed method was validated according to the International Council on Harmonization (ICH) guidelines and established to be linear in the range of 10 to 70 μg/mL with a linear regression coefficient of 0.9993. The %RSD for the method precision and system precision was found to be less than 2.0%. The %assay of the formulation is 101.52%. The LoD and LoQ were found to be 0.25 and 0.75 μg/mL, respectively. The specificity of the method established using forced degradation studies in which the drug is subjected to the stressed conditions such as thermal, acidic, basic oxidative and photolytic degradation. The developed and validated RP-HPLC method for molnupiravir takes short time and can be used for routine quality analysis of marketed Molnupiravir in capsule dosage form.